Polska refleksja stylistyczna w latach 1945-1948 = Polish stylistic reflection in the years 1945-1948 - Maćkowiak, Krzysztof (1963- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article deals with the process of reviving the Polish stylistic thought just after the end of World War II. The years 1945-1948, i.e. the period from the resumption of official scientific life in Poland after the cessation of hostilities to the establishment of the Institute of Literary Research in Warsaw at the end of 1948, is an important moment in its development. The author wants to demonstrate the specificity of the three years discussed.
Keywords: styl; historia stylistyki; dzieje językoznawstwa; style; history of stylistics; history of linguistics